A Cross-Sectional Study on Prevalence and Pattern of Dyslipidemia and Its Associated Factors among Patients with Type 2 Diabetes Mellitus - Anwar Ul Haq, Khalid Usman, Naqeeb Ullah, Tariq Hassan, Junaid Akhtar, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Diabetes mellitus type 2 (T2DM) and dyslipidemia are growing health issues. Multidimensional dyslipidemia is a characteristic of diabetes. Diabetes mellitus and dyslipidemia are comorbid conditions associated with an increased risk of cardiovascular disease. The aim of the present study was to determine the prevalence and pattern of dyslipidemia in T2DM patients. Material and Methods: This cross-sectional study was conducted on 426 type 2 diabetes mellitus patients in the Department of Family Medicine and General Surgery, Hayatabad Medical Complex, Peshawar for the duration from May 2022 to October 2022. Prior to study conduction, ethical approval was taken from institute research and ethical committee. Patient’s demographic details, laboratory findings, medications, and clinical features were recorded. Dyslipidemia was analyzed as categorical variables described as frequency and percentages. Laboratory findings included Low-density lipoprotein cholesterol (LDL-C), triglycerides (TGs), high-density lipoprotein cholesterol (HDL-C), and total cholesterol (TC). SPSS version 26 was used for data analysis. Results: Of the total 426 T2DM patients, there were 224 (52.6%) male and 202 (47.4%) females. The incidence of dyslipidemia was 92.6% among T2DM patients. Based on dyslipidemia patterns, the incidence of low HDL-C, hypertriglyceridemia, and high LDL-C were 72.4%, 62.6%, and 68.8% respectively. Diabetic dyslipidemia patterns were significantly associated with gender, hypertension, and obesity. Hypercholesterolemia and high LDL-C were significantly associated with poor glycemic control and duration of T2DM. Smoking and reduced glycemic control was related with hypertriglyceridemia. Conclusion: It has been found that the incidence of dyslipidemia among T2DM patients was 92.6%. Patients with type 2 diabetes are most likely to have low HDL-C and high triglycerides. It is strongly recommended to provide educational programs emphasizing the significance of adopting a healthy routine. Keywords: Dyslipidemia, Pattern, Type 2 diabetes mellitus